9 - Parlementaires debout : l’interface de l’opposition politique pendant la transition en République démocratique du Congo: https://doi.org/10.4314/ad.v34i3-4.63534 - Ngoy-Kango, Hubert Kabungulu (Africa Development, 2009)
The transition process initiated in the Democratic Republic of Congo (DRC) in April 1990 was followed by the emergence and proliferation of newspapers. This reality has turned the main newsstands into a privi- leged Congolese debate site where indefatigable readers commonly known as “Standing-up MP’s” gather all day long to comment the news. This paper attempts to analyse the theoretical foundation of the social phenomenon in which the poor, forming some kind of alliance, are strongly convinced that they can change the course of history by appropriating the media space in an intense struggle opposing the ruler (Mobutu) and the opposition (Tshisekedi), between 1990 and 1997. The paper concludes that the Congolese experience of “Standing-up MP’s” can serve as a model for African public space management only if it is “scholarly exploited”, that is to say probably taking it off the streets for a deeper and innovative reflection at the service of a people’s democracy that is truly participatory.